The triple oxygen isotope composition of phytoliths, a new proxy of atmospheric relative humidity: controls of soil water isotope composition, temperature, CO2 concentration and relative humidity - C. Outrequin; A. Alexandre; C. Vallet-Coulomb; C. Piel; S. Devidal; A. Landais; M. Couapel; J.-C. Mazur; C. Peugeot; M. Pierre; F. Prié; J. Roy; et al. (Climate of the Past, 2021)
Continental atmospheric relative humidity is a major climate parameter whose variability is poorly understood by global climate models. Models' improvement relies on model–data comparisons for past periods. However, there are no truly quantitative indicators of relative humidity for the pre-instrumental period. Previous studies highlighted a quantitative relationship between the triple oxygen isotope composition of phytoliths, particularly the 17O excess of phytoliths, and atmospheric relative humidity. Here, as part of a series of calibrations, we examine the respective controls of soil water isotope composition, temperature, CO2 concentration and relative humidity on phytolith 17O excess. For that purpose, the grass species Festuca arundinacea was grown in growth chambers where these parameters were varying. The setup was designed to control the evolution of the triple oxygen isotope composition of phytoliths and all the water compartments of the soil–plant–atmosphere continuum. Different analytical techniques (cavity ring-down spectroscopy and isotope ratio mass spectrometry) were used to analyze water and silica. An inter-laboratory comparison allowed to strengthen the isotope data matching. Water and phytolith isotope compositions were compared to previous datasets obtained from growth chamber and natural tropical sites. The results show that the δ′18O value of the source water governs the starting point from which the triple oxygen isotope composition of leaf water, phytolith-forming water and phytoliths evolves. However, since the 17O excess varies little in the growth chamber and natural source waters, this has no impact on the strong relative humidity dependency of the 17O excess of phytoliths, demonstrated for the 40 %–80% relative humidity range. This relative humidity dependency is not impacted by changes in air temperature or CO2 concentration either. A relative humidity proxy equation is proposed. Each per meg of change in phytolith 17O excess reflects a change in atmospheric relative humidity of ca. 0.2 %. The ±15 per meg reproducibility on the measurement of phytolith 17O excess corresponds to a ±3.6 % precision on the reconstructed relative humidity. The low sensitivity of phytolith 17O excess to climate parameters other than relative humidity makes it particularly suitable for quantitative reconstructions of continental relative humidity changes in the past.